2019
DOI: 10.1007/s11356-019-06496-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of short-term changes in street dust pollution with heavy metals in Lublin (E Poland)—levels, sources and risks

Abstract: Street dust forms as a result of the interaction of the atmosphere, lithosphere (pedosphere) and anthroposphere and can be regarded as an index of the condition of the environment in urban areas. At the end of the twentieth century, there was a significant decrease in heavy metal emissions in Europe, but not so intensive in Poland. The question arises: Is the intensity of pollution still decreasing? The study objective was to assess changes in street dust pollution with heavy metals in Lublin (E Poland) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 54 publications
0
22
0
2
Order By: Relevance
“…However, those data could falsify the real trends developing in particular districts of the city, as they strongly depended on the local atmospheric and topographic conditions [ 66 , 67 ]. Nevertheless, in our research, the average Kraków values were investigated, taking into account the long-term impact on human health.…”
Section: Discussionmentioning
confidence: 99%
“…However, those data could falsify the real trends developing in particular districts of the city, as they strongly depended on the local atmospheric and topographic conditions [ 66 , 67 ]. Nevertheless, in our research, the average Kraków values were investigated, taking into account the long-term impact on human health.…”
Section: Discussionmentioning
confidence: 99%
“…The studies were primarily focused on the influence of motor vehicle traffic on the geochemistry of soils: samples were collected in the vicinity of streets. A not very high and decreasing level of street dust pollution with heavy metals was also found (Zgłobicki et al 2018 , 2019 ).…”
Section: Methodsmentioning
confidence: 89%
“…However, seasonal and spatial variations in dust deposition rate have not been investigated properly. Zgłobicki et al (2019) assessed changes in street dust pollution with heavy metals in Lublin, Poland in the years 2013 and 2018. The sample collection sites were located within streets with a different intensity of motor traffic.…”
Section: Introductionmentioning
confidence: 99%
“…Cd, Cr, Cu, Ni, Pb and Zn concentrations were determined. Results showed that street dust in Lublin did not show contamination with Cr, Ni and Pb (Zgłobicki et al, 2019). Aghasi et al (2019) studied the relationship between soil characteristics and dust deposition rate in Gavkhouni swamp sub-basin located in Central Iran.…”
Section: Introductionmentioning
confidence: 99%